A histological assessment of the infection strategy of Exserohilum turcicum in maize. (19th November 2018) - Kotze, R. G.; van der Merwe, C. F.; Crampton, B. G.; Kritzinger, Q.
Abstract : Northern leaf blight is a lethal foliar disease of maize caused by the fungus Exserohilum turcicum . The aim of this study was to elucidate the infection strategy of the fungus in maize leaves using modern microscopy techniques and to understand better the hemibiotrophic lifestyle of E. turcicum . Leaf samples were collected from inoculated B73 maize plants at 1, 4, 9, 11, 14 and 18 days post‐inoculation (dpi). Samples were prepared according to standard microscopy procedures and analysed using light microscopy as well as scanning (SEM) and transmission electron microscopy (TEM). Microscopic observations were preceded by macroscopic observations for each time point. The fungus penetrated the leaf epidermal cells at 1 dpi and the disease was characterized by chlorotic leaf flecks. At 4 dpi the chlorotic flecks enlarged to form spots, and at 9 dpi hyphae were seen in the epidermal cells surrounding the infection site. At 11 dpi lesions started to form on the leaves and SEM revealed the presence of hyphae in the vascular bundles. At 14 dpi the xylem was almost completely blocked by hyphal growth. Hyphae spread into the adjacent bundle sheath cells causing cellular damage, characterized by plasmolysis, at 18 dpi and conidiophores formed through the stomata. Morphologically, lesions started to enlarge and coalesce leading to wilting of leaves. This study provides an updated, detailed view of the infection strategy of E. turcicum in maize and supports previous findings that E. turcicum follows a hemibiotrophic lifestyle.